Non-covalent and reversible functionalization of carbon nanotubes - Antonello Di Crescenzo; Valeria Ettorre; Antonella Fontana (Beilstein Journal of Nanotechnology, 2014)
Carbon nanotubes (CNTs) have been proposed and actively explored as multipurpose innovative nanoscaffolds for applications in fields such as material science, drug delivery and diagnostic applications. Their versatile physicochemical features are nonetheless limited by their scarce solubilization in both aqueous and organic solvents. In order to overcome this drawback CNTs can be easily non-covalently functionalized with different dispersants. In the present review we focus on the peculiar hydrophobic character of pristine CNTs that prevent them to easily disperse in organic solvents. We report some interesting examples of CNTs dispersants with the aim to highlight the essential features a molecule should possess in order to act as a good carbon nanotube dispersant both in water and in organic solvents. The review pinpoints also a few examples of dispersant design. The last section is devoted to the exploitation of the major quality of non-covalent functionalization that is its reversibility and the possibility to obtain stimuli-responsive precipitation or dispersion of CNTs.